NUTRITIVE PROPERTIES AND CONSUMER ACCEPTANCE OF SOLAR TENT AND SUN DRIED KILISHI FROM BONY-TONGUE (Heterotis niloticus, Cuvier 1829) IN A SEMI-ARID ZONE OF NIGERIA - BELLO, M.M; TEKWATA, Y.D. (Nigerian Journal of Fisheries, 2015)
This study was carried out to determine the nutritional characteristics of solar tent and sun dried kilishi of bony tongue fish (Heterotis niloticus). Thirty freshly caught samples of Heterotis niloticus from Lake Alau in Maiduguri, Nigeria with an average weight of (239.6 ± 44.9 g) were used for the study. The kilishi from the species was prepared using two different slurry formation of high (50%) and low (24.35%) proportion of groundnut dough and spices mixture respectively. The kilishi was dried in solar tent and open sun-drying in three replicates. The proximate composition was determined for moisture, protein, ash, crude fibre, and crude fat, in percentages. The prepared kilishi products were subjected to statistical analysis using two- way analysis of variance (ANOVA). The result of proximate composition indicated that the solar-dried kilishi recorded significantly higher (P > 0.05) protein content 63.03 ± 1.64, higher ash content 5.33 ± 0.81 and crude fibre (19.00 ± 0.81) while the sun dried kilishi recorded higher moisture content 7.60 ± 0.81 in sun dried product despite lower values in fibre 6.00 ± 0.08, fat 2.00 ± 0.40 and crude protein 50.76 ± 0.02. Sensory scores of solar-dried rated significantly higher values for taste, colour, flavour, appearance and general acceptability with mean scores of 5.20 ± 0.90, 6.00 ± 0.90, 5.90 ± 0.16, 6.20 ± 0.16, and 5.90 ± 0.63 respectively, while the sun dried kilishi recorded lower sensory parameters 4.30 ± 0.89, 5.10 ± 0.81, 4.90 ± 0.16, 3.40 ± 0.08, and 5.10 ± 0.81 respectively for the above parameters. It can be concluded that kilishi prepared from solar tent was the most acceptable by the taste panel while the sun dried kilishi was least accepted. However, fish kilishi from solar-dried tent form a product attractive to consumers and increased shelf-life, hence explored alternative preservation techniques to reduce fish spoilage and post-harvest losses.